Suing rapist in civil court: an alternative justice to rape victims in Malaysia / Mazlina Mahali and Muhammad Umar Abdul Razak - Mahali, Mazlina; Abdul Razak, Muhammad Umar (2014)
While rape is a criminal act punishable by imprisonment and whipping in Malaysia, criminal prosecution of the rapist is not the only legal remedy available for the rape victim. In Malaysia, Section 426(1) of the Criminal Procedure Code (Act 593) provides for the court's discretion to order convicted person to compensate the victims of the crime. The effectiveness of this provision is yet to be tested especially when no such order has been made to compensate rape victims. In the United States and the United Kingdom, civil lawsuits have become additional avenue that rape victims can take on journey towards healing. Although a civil suit cannot undo the harm the rapist has caused towards the victim, award of damages may assist the victims to cope up with the aftermath of the event such as depression, unwanted pregnancy or sexually transmitted diseases. This paper seeks to highlight the advantages of suing the rapist in civil court. It also examines the legal and practical problems of taking such action by making a critical analysis of Malaysian legal system in bringing such action in court. This paper employs a doctrinal legal research and secondary data of which the Criminal Procedure Code (CPC) is the primary source. The secondary sources for this article include decided cases, articles in academic journals, books and online databases. This paper contends that the laws are inadequate to assist the victim to sue the rapist. It is recommended that the CPC should be amended to allow the court to award compensation for acquittal cases. Furthermore, the government should enhance the scope of the legal aid assistance system in Malaysia by including civil action on sexual assault cases.